Hubungan Antara Jiwa Kewirausahaan dan Manajemen Agribisnis terhadap Keberhasilan Usaha Jamur Tiram di Kota Denpasar - Purnami Rusadi, Ni Wayan; Budi Susrusa, Ketut; Setiawan AP, I Gede (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol. 3 - No. 2 - Oktober 2015)
Oyster mushroom cultivation is one of the right businesses to be developed in Denpasar. It is based on high market demand and terraced cultivation usage system which is able to save the land. The success of oyster mushroom business is influenced by many factors such as entrepreneurial spirit ability and agribusiness management. The purpose of this study was to analyze the influence of entrepreneurial spirit and agribusiness management to oyster mushrooms business success in Denpasar. This study was conducted to oyster mushroom farmers who have at least 1000 baglog (growth media) with minimum 1 year cultivation period. The number of samples was determined by 36 respondents of mushroom farmers who were scattered in Denpasar.  The data analysis techniques which were used were SPSS and Smart PLS program. The result of the relation between variable which used PLS in the structural path coefficient showed that there was a positive and very significant relationship with more than 2,72 t-statistic value. There was a positive and very significant relationship with 5,990 t-statistic value of entrepreneurial spirit variable to oyster mushrooms business relationship. Agribusiness management to oyster mushrooms business success had a positive and very significant relationship with 6,670 t-statistic value. Entrepreneurial spirit variable to agribusiness management had a positive and very significant relationship with 49,555 t-statistic value. Goodness of fit evaluation showed that Q 2 value was 0,969 which had a meaning that 96,95% information which was in the data could be explained by model and 3,1% remaining was explained by another model. The most influenced indicator in entrepreneurial spirit variable was creative character with 0,927 outer loading value. The most influenced indicator in agribusiness management variable was agribusiness development with 0,874 outer loading value. The most influenced indicator in oyster mushrooms business variable was oyster mushroom farming income improvement with 0,866 outer loading value. This study suggests farmers to improve their entrepreneurial spirit and manage the oyster mushroom business better than before to get a maximum result. Creative character in developing this business becomes the strong main asset to compete with another oyster mushroom which comes from outside Denpasar. The government should give the policy which is related to oyster business assistance and make a plenty promotion of this healthy food therefore it can be more known by people.
Keywords: oyster mushroom, entrepreneurial spirit, agribusiness management, and business success